2011
DOI: 10.1089/hum.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Liver Gene Transfer Following Peripheral Intravascular Delivery of Adeno-Associated Virus (AAV)-5 and AAV-6 in a Large Animal Model

Abstract: Intravascular delivery of adeno-associated virus (AAV) vector is commonly used for liver-directed gene therapy. In humans, the high prevalence of neutralizing antibodies to AAV-2 capsid and the wide cross-reactivity with other serotypes hamper vector transduction efficacy. Moreover, the safety of gene-based approaches depends on vector biodistribution, vector dose, and route of administration. Here we sought to characterize the safety of AAV-5 and AAV-6 for liver-mediated human factor IX (hFIX) expression in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…In male rabbits, vector dissemination depends on the route of vector administration, vector dose and tissue tropism. The kinetics of vector clearance from semen was dose- and time-dependent but serotype-independent for AAV serotypes 2, 6 and 8 [56-58], while AAV5 displayed the shortest duration of vector shedding [58]. In all these studies, no late recurrence of AAV sequences was found in semen over several consecutive cycles of spermatogenesis, suggesting that transduction of an early spermatogenesis precursor exposed to AAV did not occur during hematogenous dissemination to the gonads.…”
Section: Translation For Pediatric Patientsmentioning
confidence: 99%
“…In male rabbits, vector dissemination depends on the route of vector administration, vector dose and tissue tropism. The kinetics of vector clearance from semen was dose- and time-dependent but serotype-independent for AAV serotypes 2, 6 and 8 [56-58], while AAV5 displayed the shortest duration of vector shedding [58]. In all these studies, no late recurrence of AAV sequences was found in semen over several consecutive cycles of spermatogenesis, suggesting that transduction of an early spermatogenesis precursor exposed to AAV did not occur during hematogenous dissemination to the gonads.…”
Section: Translation For Pediatric Patientsmentioning
confidence: 99%
“…Subsequent studies in rabbit models following intravascular injection of AAV2 or AAV8 concluded that vector dissemination to the semen is dependent on dose and time course and appears to be transient with no evidence of germ line transmission (Schuettrumpf et al, 2006;Favaro et al, 2009). Furthermore, the kinetics of clearance are also dose dependent and vary between serotypes (Favaro et al, 2011). A separate study in mice indicated that there is no evidence of germ line transmission following AAV gene delivery.…”
mentioning
confidence: 99%
“…На кроликах проверяли эффективность, безопасность, уровень экспрессии трансгена человеческого фактора IX (hFIX) в зависимости от дозы, серотипа аденоассоциированного вирусного вектора, способного вызывать у человека иммунный ответ [22].…”
Section: генная терапияunclassified